Calidad de atención y satisfacción del usuario de la Drogueria Roan, Iquitos 2022 - Rengifo Rengifo, Prisley Gianny (2023)
Our detailed work maintains as its primary objective to determine the link between the quality of care and the user satisfaction of the Roana de Iquitos pharmacies in the year 2022. Depending on the research area or the purpose, the research is quantitative or descriptive. The Pearson correlation coefficient is 0.827**, indicating the positive significant correlation, while the sigma value (binary) indicates the degree of significance, 0.000; less than 0.05. Based on these values obtained, we can confirm the hypothesis that they agree that the quality of care is significantly linked to the satisfaction of the user of Droguería Roan.